Breathe in for nothing : an interpretative phenomenological analysis exploring the influence of a Pilates warm-up in singers - Sutton, Marcelle (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.